The synergistic catalysis effect within a dinuclear nickel complex for efficient and selective electrocatalytic reduction of CO2 to CO. Issue 4 (4th January 2018) - Cao, Li-Ming; Huang, Hai-Hua; Wang, Jia-Wei; Zhong, Di-Chang; Lu, Tong-Bu
Abstract : A dinuclear nickel complex was found to be an excellent catalyst for electrocatalytic reduction of CO2 to CO. This excellent catalytic performance can be attributed to the synergistic catalysis effect between two Ni centers. Abstract : Developing cheap and earth-abundant catalysts for an efficient and selective reduction of CO2 is a promising approach to cut down the increasing emissions of CO2 and obtain valuable fuels/chemicals simultaneously. Here, we present a dinuclear nickel complex, [Ni2 L 1 ](ClO4 )4 (1, L 1 = 1, 2-bis((5, 7-dimethyl-1, 4, 8, 11-tetraazacyclotetradecan-6-yl)methyl)benzene), which shows an excellent performance for the electrocatalytic reduction of CO2 to CO, with a Faradaic efficiency of 95%, and turnover number (TON) and turnover frequency (TOF) values of 4.1 × 10 6 and 190.0 s −1, respectively. Electrochemical experiments and density functional theory (DFT) calculations revealed that the excellent catalytic performance of1 is attributed to the synergistic catalysis effect between two Ni centers within1 .